Substrate in the initial development of pajeu seedlings - Cardoso, Edvaldo Renner da Costa; Santos, Rosemery Alesandra Firmino dos; Soares, Stallone da Costa; Ribeiro, Maria Clarete Cardoso; Silva, Fred Denilson Barbosa da (Scientia Agraria Paranaensis, 2020)
Triplaris gardneriana populary know as ‘Pajeu’ is a tree species with potential for recovery of riparian forests. The aim of this work was to evaluate the emergence and initial development of saplings in different substrates. The experiment was conducted in the didactic garden of the Campus Liberdade, from the University of International Integration of Afro-Brazilian Lusophony, in the municipality of Redenção, Ceará State. A completely randomized design with six treatments and four replicates of 25 seeds was used. The substrates used were: soil, soil + humus, soil + compost, soil + manure, soil + humus + cattle manure and soil + humus + compost. Seedling emergence, emergence speed index, plant height and root length were evaluated. The substrate soil + humus + compost provided better seedling quality possibly due to the best physical characteristics, such as aerations and water retention.